Integrating AREL into EFL Speaking in Fostering Critical Thinking - Wahyuni, Sri; Syahputra, Mulyadi; Irmayanti, Defi; Rosdiana, Rosdiana; Mulyani, Mulyani; Chaira, Salwa (Teunuleh Publisher, 2024)
The purpose of this study is to integrate AREL into EFL Speaking in fostering critical thinking. The sample of this study was the grade XI 1A students of SMAN 4 Banda Aceh which is consisted of 26 students. This study was pre-experimental design with one group pre-test post-test. The instruments of this research is a test (pre-test and post-test). The finding of this study revealed 59,79 for the mean score of pre-test and 62,84 for the post-test, and the standard deviation for pre-test was 7,57 and post-test was 7,77, then the standard error of measurement for pre-test was 1,48 and 1,52 for post-test. Meanwhile, the result of this study indicate that t-test was 6,84 and t-table was 1,71. It represented that t-score is higher than t-table (6,84>1,71) which means that alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected. Thus, integrating AREL into EFL Speaking in fostering critical thinking can enhances students’ speaking ability and students got a positive impact after learning AREL in speaking grade.